Pengambilan Keputusan Pemilihan Pegawai Kecamatan Terbaik Menggunakan Metode Weighted Product (Studi Kasus: Kecamatan Ulubelu) - Tutik Ismariyati; Ranti Wulantika; Siti Mukodimah (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
Determination of the best employee in a sub-district is an activity to evaluate the performance of each employee in the ulubelu sub-district, ulubelu sub-district is one of the sub-districts in Tanggamus district. The process of assessing the selection of the best sub-district staff is done by searching for, weighting values for each attribute, which is then carried out by the perangkigan process which will determine the optimal alternative, namely the best employee. Based on the criteria set by the sub-district, among others, a. Individual performance b. Unit performance c. Absorption d. Presence of discipline. Education. Research on the Weighted product (WP) method can assist in making decisions in selecting the best employees in the Ulubelu sub-district. Of the 6 employees, the value of Doni = 0.1333 as the employee with the lowest value and febri = 0.2240 as the best employee in the ulubelu sub-district.